Master track of POLARSTERN cruise PS139/1 in 1 sec resolution (zipped, 45 MB) - Hanfland, Claudia (Alfred Wegener Institute, Helmholtz Centre for Polar and Marine Research, Bremerhaven, 2024)
Raw data acquired by position sensors on board RV Polarstern during expedition PS139/1 was processed to receive a validated master track which can be used as reference of further expedition data. During PS139/1 two Trimble Marine R750 GPS receivers and the iXBlue HYDRINS hydrographic survey inertial navigation system were used as navigation sensors. Data were downloaded from DAVIS SHIP data base (https://dship.awi.de) with a resolution of 1 sec. Processed data are provided as a master track with 1 sec resolution derived from the position sensors' data selected by priority and a generalized track with a reduced set of the most significant positions of the master track.
Keywords: 1 sec resolution